IDENTIFIKASI POTENSI BAHAYA DAN PEMANTAUAN CRITICAL POINT, (HACCP) PRODUK MAKANAN PENERBANGAN: Identification of Hazards and Critical Point Monitoring Potentials, (HACCP) Flight Food Products - Mustofa Lutfi; Bambang Dwi Argo; Sri Hartini (Fakultas Teknologi Pangan dan Agroindustri, Universitas Mataram, 2019)
ABSTRACTHACCP has been known as a system that uses a systematic and preventive approach that is shown to biological, chemical and physical hazards through anticipatory and preventive measures by no relying on inspection and testing on the final product. The application of HACCP is not only for the food industry but can be applied to the catering industry, catering services and food at hotels and restaurants. For this reason, modern food companies really need to determine quality standards for the consumers they serve. The purpose of this study was to analyze the application of HACCP on aviation food products (Aerofood ACS SUB) by identifying potential hazards and applying Critical Control Points (CCP). The methods are 1) observation of Critical Control Points (CCP) performed at receiving (CCP 1), chiller and freezer (Storage) (CCP 2), cooking (CCP 3), blast chilling (CCP 4), portioning (CCP 5). 2) Microbiological sampling consisting of random raw material samples at each arrival, hand swab samples randomly in the production and operational areas, swab equipment samples were also taken according to random, Dry good samples were taken randomly in storage, random ice cube samples , water tab samples are taken according to the sample. The company has HACCP planning as a guide for all processes that will take place within the company. All are based on the principles of HACCP for the whole process. The implementation of critical control points is in 5 places, namely receiving, storage, cooking, chilling and portioning blast. At each of these critical points, the standard critical temperature is different. Materials that do not meet the standards are rejected for further processing. In terms of microbiological hazards, it is checked by testing samples on foodstuffs, ready to eat food, dry good, air test, hand swab, production equipment, water and ice cube. The implementation of each sample test has been determined by PT. Aerofood ACS Surabaya based on standard procedures. If the results of checking is not the standards, repairs are handled or changes in the flow of handling procedures. Keywords: HACCP, CCP, Critical Limits, management system ABSTRAKHACCP telah dikenal luas diseluruh dunia sebagai suatu sistem yang menggunakan pendekatan sistimatis dan preventif yang ditunjukan kepada bahaya biologis, kimia dan fisik melalui langkah-langkah antisipatif dan pencegahan dengan tidak lagi mengandalkan pada pemeriksaan dan pengujian pada produk akhir. Penerapan HACCP tidak hanya untuk industri pangan melainkan dapat diterapkan pada industri catering dan jasa boga serta makanan di hotel dan restauran. Untuk itu perusahaan pangan modern sangat perlu untuk menentukan standart mutu untuk konsumen yang dilayaninya. Tujuan penelitian ini adalah menganalisis penerapan HACCP pada produk makanan penerbangan (Aerofood ACS SUB) dengan identifikasi potensi bahaya dan penerapan Critical Control Point (CCP). Metode yang digunakan dalam penelitian ini adalah 1) Pengamatan Critical Control Point (CCP) yang dilakukan di receiving (CCP 1), chiller dan freezer (Storage) (CCP 2), cooking (CCP 3), blast chilling (CCP 4), portioning (CCP 5). 2) Pengambilan sampel Mikrobiologi yang terdiri dari sampel raw material secara random disetiap kedatangan, sampel hand swab secara random di area produksi dan operasional, sampel equipment swab juga diambil sesuai random, sampel Dry good diambil secara random di storage, sampel ice cube secara random, sampel Water tab diambil sesuai sampel. Perusahan telah membuat perencanaan HACCP sebagai panduan untuk semua proses yang akan berlangsung didalam perusahaan. Semua disusun berdasarkan prinsip-prinsip HACCP untuk keseluruhan proses. Penerapan critical control point terdapat di 5 tempat yaitu receiving, storage, cooking, blast chilling dan portioning. Disetiap titik kritis ini, suhu kritis standart adalah berbeda beda. Bahan yang tidak memenuhi standard ditolak untuk diproses selanjutnya. Dalam hal bahaya mikrobiologi dilakukan pengecekkan melalui uji sampel pada bahan makanan, makanan ready to eat, dry good, uji udara, hand swab, peralatan produksi, air dan ice cube. Pelaksanaan masing-masing pengujian sampel sudah ditetapkan oleh PT. Aerofood ACS Surabaya berdasarkan prosedur standar. Jika hasil pengecekkan tidak memenuhi standart maka dilakukan perbaikan penanganan atau pengubahan alur prosedur handling. Kata kunci: HACCP, CCP, Batas Kritis, management system